Implementation of Pancasila Student Profile Strengthening Project Training for Early Childhood Teachers in Rangkasbitung District - Eka Setiawati; Agustinus Tandilo Mamma; Nunung Nurhayati; Y Yusdiana; Yuyum Yuningsih (CV. Media Digital Publikasi Indonesia, 2024)
This study aims to evaluate the effectiveness of the Pancasila Student Profile Strengthening training for Early Childhood Education teachers using the expository method. The expository method was chosen to provide a systematic and direct understanding of the Pancasila student profile concept, where participants received material through lectures and presentations delivered by the training facilitators. This research employed a quantitative approach by collecting data through post-training evaluation tests to measure the teachers' level of understanding of the presented material. The training results showed that 80% of the participants successfully comprehended the Pancasila student profile concept and were able to design activities relevant to its objectives, while 20% of the participants did not fully grasp the material. Factors influencing these differing results include participants' prior knowledge, professional experience, and the intensity of their engagement in the training sessions. Based on these findings, it is recommended that follow-up training adopt more interactive learning methods, such as group discussions and case studies, to enhance the understanding of participants who have not yet mastered the concepts optimally.